2017
DOI: 10.1088/1361-6560/aa9a2e
|View full text |Cite
|
Sign up to set email alerts
|

Linear energy transfer incorporated intensity modulated proton therapy optimization

Abstract: The purpose of this study was to investigate the feasibility of incorporating linear energy transfer (LET) into the optimization of intensity modulated proton therapy (IMPT) plans. Because increased LET correlates with increased biological effectiveness of protons, high LETs in target volumes and low LETs in critical structures and normal tissues are preferred in an IMPT plan. However, if not explicitly incorporated into the optimization criteria, different IMPT plans may yield similar physical dose distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(104 citation statements)
references
References 31 publications
3
100
1
Order By: Relevance
“…Cao et al have developed a method to simultaneously optimize the dose and LET d distributions of IMPT plans. Compared with the conventional IMPT plans, the plans generated using this LET d optimization strategy have elevated LET d in the target tumors and reduced LET d in the critical structures while maintaining the uniform physical dose distribution in the target tumors 36 .…”
mentioning
confidence: 99%
“…Cao et al have developed a method to simultaneously optimize the dose and LET d distributions of IMPT plans. Compared with the conventional IMPT plans, the plans generated using this LET d optimization strategy have elevated LET d in the target tumors and reduced LET d in the critical structures while maintaining the uniform physical dose distribution in the target tumors 36 .…”
mentioning
confidence: 99%
“…Besides, a recent study in prostate cancer has found that it is not possible to simultaneously meet the tumor and rectal constrains for both physical and variable RBE‐weighted dose, the latter being estimated based on in vitro cell survival data. In fact, other groups have decided to avoid the sometimes controversial concept of proton RBE completely and have tackled this problem by performing the optimization directly on LET distributions or proposing new beam orientations or treatment modalities …”
Section: Introductionmentioning
confidence: 99%
“…Besides, a recent study in prostate cancer 34 has found that it is not possible to simultaneously meet the tumor and rectal constrains for both physical and variable RBEweighted dose, the latter being estimated based on in vitro cell survival data. In fact, other groups have decided to avoid the sometimes controversial concept of proton RBE completely and have tackled this problem by performing the optimization directly on LET distributions [35][36][37][38][39] or proposing new beam orientations or treatment modalities. [40][41][42] Our proposed solution is the use of a mixed RBE model (MultiRBE) for plan optimization, where a uniform RBE is used in the target contours to ensure an adequate tumor coverage in terms of physical dose, but a variable RBE is used elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…Adding explicit terms in consideration of the LET distribution to the objective function of IMPT enables the control of the LET distribution, for example, by suppressing LET to OARs and/or concentrating LET on tumors. In fact, different versions of LET optimization techniques in this regard have been proposed by several groups, and recently, techniques have been developed to specifically incorporate the optimization of the LET d distribution into robust optimization . Using these techniques, it should become possible to further reduce the deviation not only for the OARs close to the tumor but also for the OARs distant from the tumor.…”
Section: Discussionmentioning
confidence: 99%